(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2019)
This article discusses the value of multicultural education as a framework for guiding the teaching and learning process in post-secondary education. The focus centers on English Language Learners in the United States throughout all disciplines. An analysis of the five dimensions of Critical Multicultural Education (Banks, 2019) is given along with further commentary on key areas of focus to best guide both English Language Learners and native-born students to a better understanding of the course content and each other. The ideas from this article serve as a starting place for faculty members and higher education administrators from all over the world and across disciplines who seek to re-conceptualize their classrooms and/or the college or university experience to accommodate the ever-diversifying population of students via research in multicultural education.